The impact of prebiotic supplementation in piglets and its effect on learning and memory - Mccrea, Kirste (2018)
The microbiota-gut-brain axis is known to have the ability to influence host physiology and behaviour. Studies have demonstrated an impact from gut microbiota on a variety of behaviours, such as learning and memory, largely through the use of rodent models. These impacts can be observed through changing the gut microbiota composition in ways such as administration of prebiotics, which are defined as “selectively fermented ingredients that confer benefits upon host health”. Beta-glucan is a known prebiotic that has been shown to promote beneficial microorganisms in the gut associated with effects on cognitive function. Pigs were used in this study to explore the impacts of early prebiotic supplementation on gut microbiota colonization and its subsequent effect on learning and memory. The effects on learning and memory were studied through the use of a standardized Tmaze test. Supplemented pigs performed slightly better in the acquisition phase of the test, though control pigs were faster and performed better in the reversal phase. A possible sex and phase interaction was observed, as female pigs were faster and had more correct trials in the acquisition phase than males, though the opposite trend was seen in the reversal phase. Overall, trends observed were weak and likely would not have reached significance, apart from the reversal phase of mean trials correct per session, where pigs supplemented with beta-glucan performed worse than control pigs. This may indicate that supplemented pigs were less flexible and may have a greater difficulty in adapting to a changing environment. These results could have implications for on-farm practices, though how exactly requires further investigation. In conclusion, further research into the interaction of prebiotics and he microbiota-gut-brain axis is needed, as well as how this interaction impacts learning and memory in pigs.